Acceptability Of Cookies From Lowe Banana Flour With Wheat Flour - Ramadhani Chaniago; Ainul Rizal; Dinda Vira Sastra; Citra Romi Kotesa; Dewi Ambarwati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Utilizing lowe bananas (Musa acuminata) to make flour presents an opportunity to develop more varied processed food products. In this instance, food preparations can be made by combining banana flour with other ingredients. Making cookies is one of the preparations that can be done. We wanted to know if the panelists would accept cookies made with low-fat banana flour and wheat in order to assess its potential. Usage of nearby food fixings as a substitute for wheat flour should be possible by making treats utilizing a combination of banana flour. On the decadent scale, organoleptic tests on 25 specialists delivered the most favored variety, taste, fragrance, and surface of treats in treatment C, to be specific treats made with 50% lowe banana flour and 50 percent flour.